2019
DOI: 10.3390/insects11010033
|View full text |Cite
|
Sign up to set email alerts
|

Host Immunosuppression Induced by Steinernema feltiae, an Entomopathogenic Nematode, through Inhibition of Eicosanoid Biosynthesis

Abstract: Steinernema feltiae K1 (Filipjev) (Nematode: Steinernematidae), an entomopathogenic nematode, was isolated and identified based on its morphological and molecular diagnostic characteristics. Its infective juveniles (IJs) were highly pathogenic to three lepidopteran (LC50 = 23.7–25.0 IJs/larva) and one coleopteran (LC50 = 39.3 IJs/larva) insect species. Infected larvae of the diamondback moth, Plutella xylostella (L.) (Insecta: Lepidoptera), exhibited significant reduction in phospholipase A2 (PLA2) activity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…We hypothesize that FARs bind to lipids that function as signaling molecules for a diverse range of functions including inflammation, immunity, homeostasis and reproduction. It has been proposed that most terrestrial insects lack free long-chain polyunsaturated fatty acids (LC-PUFAs) including arachidonic acid (AA), due to its role in oxidative stress (Chandra Roy et al, 2019; Stanley and Kim, 2018). Insects have high levels of reactive oxygen species (ROS), such as the superoxide anion (O 2 − ), due to their significant production of ATP in the mitochondrial electron transport chain.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that FARs bind to lipids that function as signaling molecules for a diverse range of functions including inflammation, immunity, homeostasis and reproduction. It has been proposed that most terrestrial insects lack free long-chain polyunsaturated fatty acids (LC-PUFAs) including arachidonic acid (AA), due to its role in oxidative stress (Chandra Roy et al, 2019; Stanley and Kim, 2018). Insects have high levels of reactive oxygen species (ROS), such as the superoxide anion (O 2 − ), due to their significant production of ATP in the mitochondrial electron transport chain.…”
Section: Discussionmentioning
confidence: 99%
“…In pioneering work, Kim and co-workers showed that eicosanoid signaling is targeted by EPNs and their bacteria (summarized in [ 4 ]). This has now been confirmed for Steinernema feltiae and—after using antibiotic treatment—partly attributed to their bacteria, although nematodes seem to be contributing too [ 5 ]. In addition to a reduction in cellular immunity, the activation of prophenoloxidase is used in this article as a readout for immune competence.…”
Section: Branches Of Insect Immunity That Are Targeted By Epnsmentioning
confidence: 90%
“…Because the queens were shipped live but the workers were preserved in ethanol, we only analyzed the queens for pathogens. Using established protocols 37 39 , we extracted RNA from each queen’s eviscerated body (head, thorax, and remaining abdomen) using a bead beater by first crushing each sample in individual microcentrifuge tubes, then adding 600 μL Trizol (Thermo Fisher Scientific, HQ in Waltham, MA, USA). We then extracted the RNA following the Trizol protocol (Thermo Fisher Scientific, HQ in Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Following protocols outlined in Lee et al 37 , the spermathecae from each queen was placed into 1000 µl of saline buffer, ruptured with forceps to release sperm, gently mixed with forceps, and transferred via glass Pasteur pipet into an amber chromatography vial containing 10 µL of Syber 14 (Invitrogen Live/Dead sperm staining kit #L7011; 1 mM in DMSO) diluted 1:500 into Dimethylsulfoxide (99.8%) and 10 µL propidium iodide solution (2.4 mM in water). The vial was gently vortexed for 2 s at 2000 rpm to homogenize and mix.…”
Section: Methodsmentioning
confidence: 99%